COVID 19 PANDEMIC AND HEALTHCARE SECTOR IN NORTH MACEDONIA: WHAT HAS CHANGED FOR THE HUMAN RESOURCE MANAGEMENT - Ljupco Eftimov; Tihona Bozhinovska (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2021)
The way the employees in the health care sector were managed during the period 2020-2021 was crucial for the management of the overall social and economic crisis. The most important areas from strategic human resource management that needed urgent attention during COVID 19 pandemic were: appropriate communication of the requirements of the new normal and identification of the most skillful employees for adapting to the changes and forecasting the forthcoming trends. Therefore, investigating the key activities for increasing the healthcare providers satisfaction of human resource management process during Covid 19 is an important issue and can offer significant insights for HR professionals and for the healthcare organizations. The purpose of the paper is to shed some light on the most important human resource practices during the COVID 19 pandemic and to understand how healthcare organizations had to rethink their approaches in order to maintain the motivation and commitment of the healthcare providers. The capability and willingness of the healthcare staff to stay focused and to cooperated in a dynamically changing internal and external environment was crucial for the overall healthcare sector during the pandemic. Hence, this study is trying to contribute by: identifying the key human resource (HR) issues/challenges in healthcare organizations during the pandemic, creating a theoretical model of strategic human resource management during Covid 19 in healthcare organizations and understanding which human resource (HR) practices/activities were perceived as most important for increasing healthcare providers satisfaction of the human resource management process in their organizations during the last period of turmoil.
Keywords: human resource management, pandemic, healthcare providers satisfaction of HRM, healthcare sector, key activities